Dukungan spiritualitas Berbasis Nilai-Nilai Pendidikan Kristen dalam Menghadapi Dampak Psikososial Pascabencana Alam - Sumakul, Yunita; Mongkau, Christiany; Wenur, Natalia (Peneliti.net, 2025)
Research analyzes the psychosocial impacts of natural disasters on the GMIM Maranatha Karame Congregation, explores the role of Christian Religious Education (CRE) values in the psychosocial recovery of the congregation, and the church's contribution in providing support. This study uses a qualitative approach with a case study method involving semistructured interviews with special ministers and affected congregants, as well as analysis of relevant documents. The study results show that the disaster, although without fatalities, triggered significant psychosocial impacts. Material losses, decreased income, and disruption of daily activities caused widespread anxiety and discomfort among the congregation, indicating psychological pressure even without severe trauma or loss of loved ones. The church responded proactively with spiritual guidance through communal prayers, faith-strengthening worship, and individual spiritual counseling. Church leaders instilled core Christian values such as love, hope, and perseverance. This study concludes that community-based spiritual support integrated with Christian values is a vital pillar in building and facilitating holistic postdisaster recovery.